Marionetas como recursos didácticos y su influencia en el aprendizaje de los infantes del subnivel inicial II - Romero Rizzo, Joseline Isabel (2018)
The main objective of this research work entitled MARIONETAS AS DIDÁCTICOS RESOURCES AND ITS INFLUENCE ON THE LEARNING OF INFANTS OF INITIAL SUB-LEVEL II. To know the influence of the use of puppets in learning in children of 5 years. As a research design, the case study was used with a single group consisting of 29 children. This group was influenced by the use of puppets in all classes taught. To test our hypothesis the students technique was used to compare the means of the corresponding analysis. The puppets as an educational resource in the early childhood education center is essential to achieve the optimal development of the child, since it acquires a large amount of content and appropriate values for future integration as an adult in society, and these values help create their own personality and appropriate to their environment, such as solidarity, empathy and equality. For the correct integration of this resource, it was decided to form a puppet corner, since this methodology gives children the freedom to work freely. In addition, manipulation and experimentation predominate, which helps the infant acquire a large amount of learning and achieve the objectives set. After analyzing the results of this teaching practice, we appreciate the importance of the introduction of this resource in this educational cycle, how interdisciplinary learning increases through the puppets and how it is a motivating aspect for learning. The main results point to an increase in the involvement of all children in that corner, the increase of the lexicon in most of the students in the classroom and the positive integration as reinforcement that these materials had for them.